Evidence of Characteristic Earthquakes on Thrust Faults From Paleo‐Rupture Behavior Along the Longmenshan Fault System. Issue 7 (18th July 2019) - Ran, Yongkang; Xu, Xiwei; Wang, Hu; Chen, Wenshan; Chen, Lichun; Liang, Mingjian; Yang, Huili; Li, Yanbao; Liu, Huaguo
Abstract: The rupture behavior of large‐scale thrust faults has become an increasingly important topic in active tectonic and seismic studies. This is especially true for the 2008 Wenchuan earthquake ( Mw 7.9), which occurred along the Longmenshan thrust fault (LMS) in China. While this earthquake has been the subject of many studies to date, paleoseismic studies along the LMS are still lacking. In this study, results from trenching at the town of Bailu, as well as radiocarbon and Optical‐Stimulated Luminescence dating, are used to constrain the timing of the penultimate and earlier events, respectively: 3.3 ± 0.6 to 4.4 ± 0.6 ka and 4.8 ± 0.6 to 5.8 ± 0.8 ka. Further, coseismic displacement produced by the two events is similar to that produced by the 2008 event. The results suggest that fault segments along the Yingxiu‐Beichuan and Jiangyou‐Guanxian faults likely ruptured coseismically with similar offsets and that the northern segment of the LMS possesses independent rupture behavior. The magnitude of the penultimate seismic event was likely lower than that of the 2008 event, which indicates a characteristic slip‐rupture pattern along the LMS. Key Points: New trenches were opened for paleoseismic studies on the Longmenshan thrust fault Trenches reveal evidence of three paleoseismic events with similar recurrence intervals and coseismic offsets Longmenshan thrust fault shows a characteristic coseismic slip‐rupturing pattern